Self-control at work and dominate occupational values. - Terelak, Jan Felicjan; Hys - Martyńska, Anna (Studia Psychologica: Theoria et praxis, 2004)
This empiric article concerns relationship between sense of self-control and work valuation. Theoretical basis of hypothesis was the M. Kohna, C. Schoolera Theory of Selfcontrol and K.H. Seifert and C. Bregmann Concept of Jobs Value. Two occupational groups: workers from National Library and editorial office of State Scientific Publishing House were evaluated by following methods: M. Kohna, C. Schoolera Self-control Questionnaire, X. Gliszczyńska I-E Scale, K. H. Seifert, C. Bergmann adapted by A. Zalewska orientation on jobs value scale. The results obtained from 49 editorial employees (aged 25-55) were considered in the research. Statistic analysis of the data revealed that people with a higher level of occupational self-direction concentrate at work values and work aspects which are related to the internal labour characteristics, whereas people with a lower self-direction level focus more on labour characteristics external to the essence of a particular job.